RESEARCH ON MOBILE CONSUMER HABIT AND ATTITUDE TOWARDS FEMTOCELL SERVICES - Novika Candra Astuti; Lamhot S.P. Simamora (Jurnal Manajemen Indonesia, 2016)
Femtocell is the new technology that may offer competitive value to mobile service providers for increasing their market share, retain the consumers and lower the operational cost ini providing the better signal especially inside building (indoor). This study investigate the habit and attitude of mobile consumers int two specific areas in Bandung; Buah Batu Regency and Mitra Dago-Antapani, toward the use of femtocell value and services. This study also considers the marketing implication the success of femtocell deployment in the future